Character Building Through Hidden Curriculum: Caregivers’ Tahajjud Exemplarity and Time Discipline in Pesantren - Sahrandi, Akhmad; Taufiq, Muhammad; Lubis, Kholid Ahmad Shabri (Jurnal Pendidikan Islam, 2026)
The persistent gap between formal character instruction and the actual moral conduct of students often stems from a lack of authentic role modeling within the educational environment. This study examines the mechanisms and impact of caregivers’ exemplary living (uswatun hasanah) as a form of hidden curriculum within pesantren character education. It focuses on three inquiries: the manifestation of exemplary behavior in Tahajjud rituals and time management; the internalization process among students and teachers; and its broader impact on community culture. Employing an ethnographic qualitative approach at At-Taqwa Pesantren, data were gathered through participant observation, in-depth interviews, and documentary studies. Findings reveal three pillars of the hidden curriculum: authentic spiritual consistency in Tahajjud, time discipline as an expression of integrity, and transparent sincerity. These values are internalized through observational modeling, emotional identification, and behavioral normalization. Consequently, a mutually reinforcing educational ecosystem emerges, where exemplarity serves as the “soul” or ethos driving formal processes. This research concludes that effective character education relies heavily on an authentic, integrated hidden curriculum. Crucially, educational institutions must prioritize recruiting mentors who possess both academic competence and profound moral character, recognizing that every interaction and behavior serves as the most persuasive curriculum for student development.